P-327 Prolonged Restraint Stressor Exposure in Outbred CD-1 Mice Impacts Microbiota, Colonic Inflammation, and Short Chain Fatty Acids in Colonic Inflammation. (February 2017) - Maltz, Ross; Keirsey, Jeremy; Mackos, Amy; Kim, Sandra; Somogyi, Arpad; Gharaibeh, Raad; Moore, Cathy; Bailey, Michael
Abstract : Background: Inflammatory bowel diseases (IBD), which include Crohn's disease and ulcerative colitis, involve disrupted homeostatic interactions between the gut microbiota and the mucosal immune system as a result of multiple genetic and environmental factors. Stress is one potential environmental trigger in IBD. Although the mechanisms are not well defined, it is known that exposure to stress can change the composition of the GI microbiota, leading to increased inflammation. To address this, we sought to determine whether microbially-produced short chain fatty acids (SCFA) can mediate the impact of stress on the gut microbiota, and modulate host inflammatory responses to a colonic pathogen. Methods: Male specific pathogen-free (SPF) CD-1 mice (6–8 weeks old) were either exposed to a prolonged restraint stressor or left undisturbed as a control. Mice did not eat or drink while in the restraining tube; thus, a second control group was deprived of food and water, but not restrained. The prolonged restraint stressor involved physical confinement overnight on 6 consecutive nights. Mice were orally challenged with Citrobacter rodentium the morning after the first night of confinement; control mice were not infected with C. rodentium. Tissue was harvested on day 6 post-infection. SCFA (acetic acid, butyric acid, and propionic acid) levels were quantified from fecal samples by gas chromatography-mass spectrometry (GC-MS). Semi-quantitative real time PCR was performed on proximal colonic tissue to assess SCFA receptors GPR41, GPR43, and GPR109A mRNA, as well as inflammatory (TNF-α, IL-1β, and iNOS) and anti-inflammatory cytokine expression (TGFβ). DNA was extracted from colonic tissue and amplified for 16S V3-4 rRNA gene sequencing via Illumina MiSeq. Alpha diversity, beta diversity and taxonomic analyses were used to characterize microbial communities. Results: Stressor exposure was associated with significantly increased markers of colonic inflammation in C. rodentium-infected mice and also significantly altered the alpha and beta diversity of the gut microbiota in both uninfected and C. rodentium-infected mice ( P < 0.05). Stressor exposure caused an increase in relative abundance of Aerococcus, Corynebacterium, Jeotgalicoccus, and Staphylococcus and a decrease in Mucispirillum ( P < 0.05). Stressor exposure without pathogen exposure decreased acetic acid, butyric acid, and propionic acid ( P < 0.05). Infection with C. rodentium did not significantly change SCFA levels in the colon, but C. rodentium did increase colonic GPR41 and GPR109A mRNA expression ( P < 0.05). GPR109A expression was also increased by stressor exposure ( P < 0.05), whereas GPR41 expression was reduced by stressor exposure in the infected animals ( P < 0.05). When correlation analyses were conducted, propionic acid levels positively correlated with GPR109a expression, which also positively correlated with IL-1β and iNOS gene expression. Expression of iNOS was positively correlated with colonic histopathology scores. Conclusions: Pathogen-induced colitis and a prolonged stressor significantly alter the gut microbiota, the production of SCFAs and the expression of their colonic receptors. Data suggest that iNOS is associated with heightened colonic inflammation, and its expression is related to increased propionic acid and GPR109A in stressor-exposed mice. Our study suggests that this murine model can be used to further study the impact of the microbiota, SCFAs and receptor signaling on colonic inflammation.